Varieties of Trust - Eric M. Uslaner (Fondazione Eni Enrico Mattei (FEEM), 2005)
There are multiple dimensions of trust. The standard meaning I call strategic trust. But more important is moralistic trust, which does not stem from experience, but rather is learned early in life and is largely stable over time. Moralistic trust leads people to do good works such as contributing to charity and volunteering time and to be more tolerant toward minorities. Countries with high levels of trust have better functioning governments and redistribute resources from the rich to the poor. Moralistic trust rests upon a foundation of economic equality: The most equal countries have the highest levels of trust.
Keywords: 330; Trust; Social capital; Tolerance; Civic engagement